Glaucoma: role of neuroprotective agents - Pandey, Achyut N.; Singh, Parul; Kaul, Ameeta; Sharma, P. D. (International Journal of Basic & Clinical Pharmacology, 2017)
Glaucoma is an optic neuropathy, considered as the second leading cause of blindness worldwide. Glaucoma is characterized by selective death of retinal ganglion cells (RGC) and a progressive loss of vision. Elevated intraocular pressure (IOP) is one of the most important risk factors for developing glaucoma and hence we mainly focus on lowering IOP to arrest the progression of glaucoma. However, many patients continue to demonstrate a clinically downhill course despite the control of initially raised IOP. In fact, some patients develop what is called normal tension glaucoma, not associated to an increased IOP. This emphasizes that several pressure-independent mechanisms are responsible for the development and progression of glaucomatous neuropathy and that high IOP and vascular insufficiency in the optic nerve head are only risk factors for the development of glaucoma, and are not the only target for the treatment of glaucoma. The reason is that the process of RGC death is thought to be biphasic, and the primary injury is followed by a slower secondary degeneration related to a noxious environment surrounding the apoptotic cells. This environment is characterized by changes in the extra-cellular ionic concentrations, increased amounts of free radicals, neurotrophins (NT) depletion and increased glutamate-induced excitotoxicity due to high extra-cellular glutamate levels, which binds to N-methyl-D-aspartate (NMDA) receptors leading to an abnormally high intracellular Ca2+ concentration. Neuroprotection is a process that attempts to preserve the remaining cells that are still vulnerable to damage, and the main aim of neuroprotective therapy is to employ pharmacologic or other means to attenuate the hostility of the environment surrounding the degenerating cells, or to supply the cells with the tools to deal with this aggression, providing resilience to the insult. Several agents have been reported neuroprotective in glaucoma, both in clinical assays, such as Ca2+ channel blockers, and in experimental studies, such as betaxolol, brimonidine, NMDA antagonists, nitric oxide synthase inhibitors, NT and Ginkgo biloba extract. Most neuroprotective agents for glaucoma have proved beneficial effects over RGC, not showing effects over IOP. However, when analyzing classically used medications for glaucoma, it becomes difficult to understand if its effect over the progression of glaucoma is due to neuroprotective pathways or by means of lowering IOP. The ideal anti-glaucoma drug would be one that when applied topically, reduces IOP, but also probes to reach the retina in appropriate amounts, and activates specific receptors in the retina to attenuate RGC death. In this review, we will examine currently advocated neuroprotective drug-based strategies in the potential management of glaucoma.